ADOLECENTES SPORTING HABITS OF THE CITY OF NOVO HAMBURGO-RS. A STUDY ON THE MOTIVATION TO PRACTICE PHYSICAL SPORTS ACTIVITY. (Fiep Bulletin - online, 2012)
The practice of physical and sports activities on a regular basis, has been considered as one of the relevant components within a healthy lifestyle. The present study attempts to establish who motivates 15, 16 and 17 year old teenagers in the public education system in the city of Novo Hamburgo, in the State of Rio Grande do Sul, to practice physical and sports activity. This investigation is characterized as quantitative, of non-experimental methodology, has as a study type, the Transversal one and a questionnaire as an instrument. As results, it was found that the ones who motivate teenagers to practice activities, in their own opinion, are friends, themselves, family and the teacher.
Keywords: Teenager; Exercise; Sport